Effect of Continuous and Interval Exercise on The Expression of Heat Shock Proteins in Animal Model - Shabkhiz, Fatemeh; Goodarzi, Mahmood; Rajabi, Reza; Shahrokhi, Somayyeh (Asian Journal of Chemistry, 2010)
In this study, elderly female animals as a model have been selected to evaluate the level of heat shock protein molecules in the spleen before and after different types of trainings (continuous and interval). It is noticed that the interval training could highly increase the heat shock protein level in both mid and post test, while a significant increase was noticed in the post test continuous training, but not in its mid test. Making generalization about this model it is concluded that in the elderly female animals, in case heat shock protein level is normal, the body is in a healthy condition and training can preserve the normal level of heat shock protein. Being in agreement with the previous results which confirmed an increase in the heat shock protein level, in muscles, healthy heart, liver and brain after exercise, present study indicated an increase also in spleen.